Mergers & acquisitions : theory, strategy, finance - Ibrahimi, Mohammed (Hoboken, New Jersey : Wiley, 2018)
This book deals with corporate mergers and acquisitions by analyzing the financial and strategic aspects. It starts with a chronological justification of the evolution of external growth operations and ends with case studies in order to put into practice the theoretical contribution of the previous titles. Through this book, we wish to detail the types of mergers and acquisitions, their modes, their motivations, their consequences and their performances. First of all, we propose a panoply of scientific research, methodological explanations and logical structuring to expose a subject of experience considered for a long time as a phenomenon in finance. Then, through a sample of 90 mergers or acquisitions, we analyze the effects of these transactions on French companies.
Part 1 : Taxonomy of mergers and acquisitions and the evolution of managerial thought -- Chapter 1 : Strategic evolution of mergers and acquisitions -- Chapter 2 : Growth methods and responses -- Part 2 : Mergers and acquisitions strategies : cause and effect -- Chapter 3 : Asset transfers : causes and consequences -- Chapter 4 : Mergers/acquisitions : motivation and performance -- Part 3 : Value creation and measurement methods -- Chapter 5 : Synergy in mergers and acquisitions -- Chapter 6 : Measurement methods for value creation -- Part 4 : The French market : analyses and case studies -- Chapter 7 : Observations and lessons from the French merger/acquisition market -- Chapter 8 : Value creation in the Sanofi-Aventis merger.
Online resource; title from PDF title page (EBSCO, viewed August 7, 2018)
Keywords: Consolidation and merger of corporations; Electronic books